(untitled) (Panacea Journal of Medical Sciences, 2022)
Background: In India tuberculosis is a communicable infectious bacterial disease caused by Mycobacterium tuberculosis causing major public health problem. The present study is a prospective study of various haematalogical parameters in sputum positive pulmonary tuberculosis. Materials and Methods: The study included thirty patients of fresh pulmonary tuberculosis with sputum positive for acid fast bacilli (AFB). It was conducted for a period of three months in the institution of Coimbatore medical college hospital. The various hematological parameters were analyzed by means of automated cell counter and peripheral smear examination. The smears were stained with Ziehl Neelsen stain used to identify acid-fast organisms mainly mycobacteria. Results : The study included 30 cases of newly detected pulmonary Tuberculosis patients who were positive for acid fast bacilli out of which 6 were females and 24 were males. Maximum number of cases were found in between 40-60 years of age. The commonest hematological findings were anemia 100% then raised ESR 93.33%, followed by, thrombocytosis 16.66%., neutrophilia 56.66%, leukocytosis 56.66% and lymphocytosis 6.66%. The commonest peripheral smear picture was microcytic hypochromic anemia 63.33% followed by normocytic normochromic anemia 30% then macrocytic anemia 6.6%. Conclusion: Various changes in haematological parameters has been observed in patients with patients who are sputum positive for pulmonary tuberculosis. The present study is being done to evaluate the hematological profile in tuberculosis and analyse the variations in hematological manifestations. These parameters acts as a valuable tool to reduce the morbidity and mortality thus aids in improving then prognosis in patients with pulmonary tuberculosis.